Characterization of cockle shells and evaluation of post-intramuscular implantation of cockle shell demineralized bone matrix composite in rat and rabbit models - Awang Junaidi, Awang Hazmi (2009)
The potential of cockle (Anadara granosa) shells as an alternative biomaterial for the development of bone graft substitute was evaluated in three interlinked experiments. In the first experiment, cockle shells from there different sources (Kuala Selangor, Selangor; Juru, Penang; Klebang, Malacca) along the West Coast of Peninsular Malaysia were processed to form the cockle shell powder (CSP) with the size of <420 11m and characterization of the mineral composition and the physicochemical properties of the shells were performed. The composition of major minerals namely Ca, C, Mg, Na, P and K, and other trace minerals; Fe, Cu, Ni, Si, Zn and B were determined by using standard methods of elemental analysis. Meanwhile, the physicochemical properties of the shells were determined using Powder X-Ray Diffraction (PXRD) and Fourier Transform Infrared Spectroscopy (FTIR) analysis. The physicochemical properties of coral (Porites sp.) obtained from different sea depths of 5 m, 10 m, and 15 m were compared. The results showed that the mineral composition of the cockle shells from three different sources was consistent with no significant differences (p>0.05) in most of the minerals being evaluated. Overall, cockle shells are composed of 98.78 % Ca+C, 0.046 % Mg, 0.92 % Na, 0.018 % P, 0.04 % K and 0.19 % other minerals including Fe, Cu, Ni, Zn, Band Si. The results of PXRD and FTIR analysis proved that cockle shells and coral (Porites sp.) shared similar physicochemical properties regardless of their sources. The results also demonstrated high purity and crystallinity possessed by CSP, and the presence of calcium carbonate (CaC03) which was the major functional group forming the cockle shells. In the second experiment, CSP was combined with demineralized bone matrix (DBM)in 1:1 ratio (w/w) with an aid of starch as the binder to form a rectangular shape (0.5 X 0.5 0.2 em) cockle shell-DBM composite. The DBMwas produced from the long bone of adult male Sprague-Dawley rats that had been demineralized in 0.6 M hydrochloric acid (HCI). The responses toward the composite were evaluated in an intramuscular implantation model in rats. Twelve adult male Sprague-Dawley rats were used for the implantation purposes. The composites were implanted at the quadriceps muscles of left hind leg, meanwhile the control pellets composed of only esp, with the same shape and size were implanted at the same site of contra lateral leg. Radiographs were taken immediately after the surgery and followed at week one, four and six post-implantation. Four rats were sacrificed at each experimental interval, where the implants with the surrounding muscle tissue were harvested for histological evaluation. The radiographic findings showed that both the composite and the control underwent reduction in the size and radio-density with time. In contrast with the control that was only visible up to week four, the composite remained visible on the radiographs at the end of week six post implantation, with slight increase in radio-density. Histological evaluation found no signs of rejection toward both types of implants and bone formation were only discovered in histological sections of muscle implanted with the composite. In the third experiment, three types of cockle shell-DBM composite with different composition namely composite A: eSP+DBM (wjw, 9:1); composite B:eSP+DBM (wjw, 7:3)and composite c. csr- DBM+collagen type I (wjw, 7:2.9:0.1)cylindrical blocks in shape (1 em x 0.4 cm) were produced by using polyvinylpyrrolidone (PVP) as a binder. The DBMwas produced from the long bone of adult male New Zealand White rabbit through the same process as described in the second experiment, meanwhile collagen type I in composite e is a commercial product originated from rabbits of the same species. Evaluation on the morphology of the composite was done prior to implantation in intramuscular sites of rabbits. Twenty seven adult male New Zealand White rabbits were used for implantation purposes where they were divided into three groups of nine rabbits each. Each rabbit from each group was implanted with three composite A, Band C respectively in the muscle pouches created which were 15 mm length x 6mm depth, 25 mm from vertebral spine and 25 mm apart, at the right paravetrebral muscle. Three control materials composed of 100%CSP with the same design were implanted at the same position of the contra lateral muscle. The responses towards the implants post implantation were macroscopically and microscopically evaluated. Radiographs were taken immediately after the surgery and followed at week one, four and twelve post implantation. Three rabbits from each group were sacrificed at week one, four and twelve post implantation, and gross and histological evaluation were performed on the implant and the surrounding muscle tissues. The SEM results showed that the composite possessed a porous structure with poor interconnectivity. Macroscopic evaluation discovered that all composites regardless of types underwent apparent changes in size, shape and morphology after four weeks of implantation based on the radiographic findings. Gross examination demonstrated good healing responses at the implantation sites without apparent signs of rejection towards all type of composites in all animals. The microscopic findings showed that the responses toward the composites relied on the formulation of the composites and the duration of implantation. Histomorphometric results evidenced that osteoinductivity of composite Band C were significantly (p<O.05) higher than that of composite A after four weeks of implantation. It can be concluded that cockle shells are viable materials that have a high potential to be used as an alternative biomaterial for the development of future bone graft substitutes based on its mineral composition and physicochemical properties. Cockle shells-DBM composite is biodegradable and biocompatible in nature, and possessed an osteoinductive potential based on the responses after intramuscular implantation in both rat and rabbit models. Finally, the bone forming potential of the composite is proportional to the amount of DBM being incorporated in one unit composite.